1997
DOI: 10.1021/ja970335p
|View full text |Cite
|
Sign up to set email alerts
|

The π-Donor Ability of the Halogens in Cations and Neutral Molecules. A Theoretical Study of AX3+, AH2X+, YX3, and YH2X (A = C, Si, Ge, Sn, Pb; Y = B, Al, Ga, In, Tl; X = F, Cl, Br, I)

Abstract: Quantum mechanical ab initio calculations at the MP2/VDZ+P level of theory (for some molecules at MP2/VTZ+D+P) are reported for the cations AX3 + and AH2X+ (A = C, Si, Ge, Sn, Pb; X = F, Cl, Br, I) and the isoelectronic neutral Lewis acids YX3 and YH2X (Y = B, Al, Ga, In, Tl; X = F, Cl, Br, I). The π-donor ability of the halogens given by the p(π) population at atom A increases for all cations with F < Cl < Br < I, which is the opposite to what has been reported in a recent study of Olah and co-workers (J. Am.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
132
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 24 publications
22
132
0
Order By: Relevance
“…The geometries and harmonic frequencies of the FSiH 2 + isomer 3 and of the H-SiF 2 + isomer 6 of C 2v symmetry are also in good agreement with previous HF, [14][15][16] MP2 [10,17] and CASSCF [18] ab initio studies and are again typical of covalent structures. On the other hand, the bond lengths, harmonic frequencies and dissociation energies of the (Si,H 2 ,F) + isomers 4 and 5, and of the (Si,H,F 2 ) + isomers 7 and 8, point to ion-molecule complexes between ground-state SiF + ( 1 Σ + ) [19] and H 2 (4) or HF (7), and ground-state SiH + ( 1 Σ + ) [20] and HF (5) or F 2 (8).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The geometries and harmonic frequencies of the FSiH 2 + isomer 3 and of the H-SiF 2 + isomer 6 of C 2v symmetry are also in good agreement with previous HF, [14][15][16] MP2 [10,17] and CASSCF [18] ab initio studies and are again typical of covalent structures. On the other hand, the bond lengths, harmonic frequencies and dissociation energies of the (Si,H 2 ,F) + isomers 4 and 5, and of the (Si,H,F 2 ) + isomers 7 and 8, point to ion-molecule complexes between ground-state SiF + ( 1 Σ + ) [19] and H 2 (4) or HF (7), and ground-state SiH + ( 1 Σ + ) [20] and HF (5) or F 2 (8).…”
Section: Resultssupporting
confidence: 87%
“…[6,7] Concerning the structure of cations such as AHX + , AX 2 + , AH 2 X + , AHX 2 + and AX 3 + (A = C, Si, Ge, Sn, Pb; X = monovalent group), they are usually assumed to be "regular" covalent structures and the conceivable role of ion-molecule complexes such as A + -(HX), AH + -(HX) or AX + -(H 2 ) is still essentially unexplored. As a first step in this direction, stimulated by our continuing interest in the chemistry of fluorinated cations, [8] we report here an ab initio study on the heavier congeners of the fluoromethyl cations CH 2 F + , CHF 2 + and CF 3 + , which are known to possess covalent structures of C 2v or D 3h symmetry, [9][10][11][12] . Therefore, our calculations provide additional examples of only "seemingly familiar" [1] compounds of group XIV and confirm the crucial role of noncovalent isomers in the gas-phase ion chemistry of the heaviest elements: germanium, tin and lead.…”
Section: Introductionmentioning
confidence: 99%
“…However, cations bearing an NR 2 group are better addressed as iminium salts. For the completely halogen-substituted CX 3 + ions it was predicted [1,2,16,17] that the stabilizing effect of the halogen substituent increases from F to I (in opposition to the earlier conclusions [18] ). The theoretical prediction was confirmed by the synthesis [17] and crystal structure of a room-temperature stable CI 3 + salt.…”
Section: Introductionmentioning
confidence: 97%
“…We attribute the small high-field shift of D(d 13 C) of 11-21 ppm in 1 to the presence of the heavy bromine atom at the carbenium center and the inverse halogen dependence of the shifts of compounds with a heavy halogen substituent. [16,27] Compound 1 is very sensitive to air and moisture, but is stable at room temperature in the solid state and for at least 20 h in CH 2 Cl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Of the ions investigated in this study, only the silicenium ions that are stabilized by pnicogens from the third to Introduction Heteroatom-stabilized carbenium ions, in which the positively charged carbocation acts as a strong p(p)-acceptor that is stabilized by up to three main group elements that act as p(p)-donors of varying strengths, have been one of the most interesting and thoroughly examined systems recently. [1] In this respect, the structures and energies of monosubstituted and triply substituted carbenium ions of the general type [H 2 C-(XH n )] and [C(XH n ) 3 ] have been of particular interest, and complexes with pnicogens (n 2), [2,3] chalcogens (n 1), [3±5] or halogens (n 0) [3,6] as heteroatoms X were studied in more detail. It was concluded that the p(p)-donor ability of such substituents plays a crucial and at times controversial role in establishing trends in the stabilization exerted by a particular p(p)-donor within a group or a row of the periodic system.…”
mentioning
confidence: 99%